2017
DOI: 10.15406/jabb.2017.02.00048
|View full text |Cite
|
Sign up to set email alerts
|

Audible Sound in Form of Music Can Influence Microbial Growth, Metabolism and Antibiotic Susceptibility

Abstract: Effect of a type of Indian classical music (Raag Malhar) comprised of the sound corresponding to a frequency range of 41-645 Hz, on microbial growth, production of certain important metabolites and antibiotic susceptibility was investigated. All the bacteria and yeasts used as test organisms were found to register better growth under the influence of music, except Serratia marcescens. Music treatment was also found to promote production of bacterial pigments (prodigiosin and violacein) whose production is norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Besides, similar findings to the sound differently on sound with different frequencies, amplitude, and intensity could produce a different response from the same organism (Kothari, 2017). The results in this present study suggest that the chondrocytes exposed to the Quranic recitation show the most favorable effects compared to the chondrocytes exposed to other sounds.…”
Section: Wound Healingsupporting
confidence: 58%
See 1 more Smart Citation
“…Besides, similar findings to the sound differently on sound with different frequencies, amplitude, and intensity could produce a different response from the same organism (Kothari, 2017). The results in this present study suggest that the chondrocytes exposed to the Quranic recitation show the most favorable effects compared to the chondrocytes exposed to other sounds.…”
Section: Wound Healingsupporting
confidence: 58%
“…The sound was used in the therapeutic strategy to improve the cell's proliferation in the hippocampus (Lee et al, 2016). It can also affect microbial growth and metabolism of an organism to a noticeable extent (Sarvaiya & Kothari, 2015;Kothari, 2017). All these examples suggest that sound may directly or indirectly affect humans, physically and spiritually.…”
Section: Introductionmentioning
confidence: 99%
“…All the three gram-negative bacteria used in this study were multidrug resistant, and their antibiogram has previously been reported by us (Joshi et al, 2019;Patel et al, 2019a). Additionally, C. violaceum and S. marcescens strains mentioned here have been reported by us as beta-lactamase producers (Sarvaiya & Kothari, 2017).…”
Section: Bacterial Strainssupporting
confidence: 55%
“…There are many records documenting how sound affects biomolecules in water solutions, single-cells and even whole organisms, plants especially [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. One study showed that audible sound in the form of music (38–689 Hz) was able to affect growth, metabolism and antibiotic susceptibility of prokaryotic as well as eukaryotic microbes [ 8 , 9 ]. A study about the influence of sound on chrysanthemum plants, discovered that sound wave accelerated the synthesis of RNA and soluble protein, indicating that some stress-induced genes might be switched on under sound stimulation.…”
Section: Introductionmentioning
confidence: 99%